2023
DOI: 10.1186/s12889-023-15843-0
|View full text |Cite|
|
Sign up to set email alerts
|

Cross-sectional survey of attitudes and beliefs towards dementia risk reduction among Australian older adults

Abstract: Background Little is known about what drives older adults’ motivation to change their behaviour and whether that is associated with their personal dementia risk profile. Our aims were to (i) understand what sociodemographic factors are associated with older Australians’ motivation to change behaviour to reduce their dementia risk, and (ii) explore the relationship between socio-demographic factors and motivation to reduce dementia risk with health- and lifestyle-based dementia risk scores in ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…On the other hand, there are reports that vitamin D supplementation alone does not improve sarcopenia in community-dwelling older adults [73], so further results on nutritional supplementation are needed. Regarding lifestyle modification, there are reports that younger older adults are more motivated to make lifestyle changes to reduce their risk of dementia [74] and that healthy lifestyle modification programs, with particular emphasis on dietary changes, can help prevent CVD events, including myocardial infarction and stroke, in older adults living in the community [75].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, there are reports that vitamin D supplementation alone does not improve sarcopenia in community-dwelling older adults [73], so further results on nutritional supplementation are needed. Regarding lifestyle modification, there are reports that younger older adults are more motivated to make lifestyle changes to reduce their risk of dementia [74] and that healthy lifestyle modification programs, with particular emphasis on dietary changes, can help prevent CVD events, including myocardial infarction and stroke, in older adults living in the community [75].…”
Section: Discussionmentioning
confidence: 99%
“… Demographics : Following previous national survey studies [ 23 25 ], nine questions regarding participants’ age, gender, country of birth, marital and employment status, and postcode. Educational attainment was split into low (minimal or no formal education), middle (intermediate levels of education such as secondary education or vocational training) and high attainment (completed tertiary education).…”
Section: Methodsmentioning
confidence: 99%
“…Demographics, health status and current technology use questions in this study were adopted from previous national survey studies conducted with older Australians [23][24][25]. The latter questions on appraisal and acceptance of VR technology were further adapted from the Technology Acceptance Model (TAM) [17] to assess participants' perceptions of technology acceptance and usability according to our study's objectives.…”
Section: Measurementmentioning
confidence: 99%
“…Despite not reaching a population-level increase in awareness of dementia risk reduction, the study demonstrated that exposure to the campaign led to a greater awareness and motivation for behavior change. However, effective population-level prevention requires both individual motivation for behavior change, along with public health action supported by widespread societal and policy change which poses additional systemic challenges ( 6 , 21 , 22 ).…”
Section: Introductionmentioning
confidence: 99%